2006
DOI: 10.1038/nm1485
|View full text |Cite
|
Sign up to set email alerts
|

Activation of β2-adrenergic receptor stimulates γ-secretase activity and accelerates amyloid plaque formation

Abstract: Amyloid plaque is the hallmark and primary cause of Alzheimer disease. Mutations of presenilin-1, the gamma-secretase catalytic subunit, can affect amyloid-beta (Abeta) production and Alzheimer disease pathogenesis. However, it is largely unknown whether and how gamma-secretase activity and amyloid plaque formation are regulated by environmental factors such as stress, which is mediated by receptors including beta(2)-adrenergic receptor (beta(2)-AR). Here we report that activation of beta(2)-AR enhanced gamma-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
191
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 213 publications
(206 citation statements)
references
References 47 publications
15
191
0
Order By: Relevance
“…Remarkably, we found in our recent study that β2-adrenoceptor signaling, which mediates the stress response in animals, regulates γ-secretase activity and senile plaque formation in vivo [67]. Our present study shows that extracellular signals, at least those mediated by RTKs, could increase Aβ production by enhancing BACE activity.…”
Section: Discussionsupporting
confidence: 68%
“…Remarkably, we found in our recent study that β2-adrenoceptor signaling, which mediates the stress response in animals, regulates γ-secretase activity and senile plaque formation in vivo [67]. Our present study shows that extracellular signals, at least those mediated by RTKs, could increase Aβ production by enhancing BACE activity.…”
Section: Discussionsupporting
confidence: 68%
“…We have previously reported that β 2 -AR associates with PS1 and that agonist-induced endocytosis of β 2 -AR enhances trafficking of γ-secretase to late endosomes and increases Aβ production [23]. We hypothesized that a similar interaction-based mechanism might also apply here.…”
Section: Dor Activation Leads To Enrichment Of Bace1 and γ-Secretase mentioning
confidence: 80%
“…We have previously reported that activation of DOR enhances γ-secretase activity in vitro [23]. Here, we first investigated whether activation of DOR specifically affects secretase activities for Aβ production.…”
Section: Activation Of Dor Enhances Bace1 and γ-Secretase Activities mentioning
confidence: 99%
See 2 more Smart Citations